Histone Lysine Methylation Modification and Its Role in Vascular Calcification - Cao, Ye-Chi; Shan, Su-Kang; Guo, Bei; Li, Chang-Chun; Li, Fu-Xing-Zi; Zheng, Ming-Hui; Xu, Qiu-Shuang; Wang, Yi; Lei, Li-Min; Tang, Ke-Xin; Ou-Yang, Wen-Lu; Duan, Jia-Yue; et al. (Frontiers in Endocrinology, 2022)
Histone methylation is an epigenetic change mediated by histone methyltransferase, and has been connected to the beginning and progression of several diseases. The most common ailments that affect the elderly are cardiovascular and cerebrovascular disorders. They are the leading causes of death, and their incidence is linked to vascular calcification (VC). The key mechanism of VC is the transformation of vascular smooth muscle cells (VSMCs) into osteoblast-like phenotypes, which is a highly adjustable process involving a variety of complex pathophysiological processes, such as metabolic abnormalities, apoptosis, oxidative stress and signalling pathways. Many researchers have investigated the mechanism of VC and related targets for the prevention and treatment of cardiovascular and cerebrovascular diseases. Their findings revealed that histone lysine methylation modification may play a key role in the various stages of VC. As a result, a thorough examination of the role and mechanism of lysine methylation modification in physiological and pathological states is critical, not only for identifying specific molecular markers of VC and new therapeutic targets, but also for directing the development of new related drugs. Finally, we provide this review to discover the association between histone methylation modification and VC, as well as diverse approaches with which to investigate the pathophysiology of VC and prospective treatment possibilities.